Elevation of Serum Cytokine Profiles and Liver Metabolomic Normalization in Early Convalescence of COVID-19 Patients - Lou, Yan; He, Xiaoying; Deng, Mingxia; Hu, Xingjiang; Yang, Xi; Liu, Lin; Hu, Yunzhen; He, Lingjuan; Wang, Jiali; Zhang, Li; Zhao, Qingwei; Lu, Xiaoyang; et al. (Frontiers in Medicine, 2021)
Coronavirus disease 2019 (COVID-19) has become a global public health concern. We aimed to study the cytokine profile during the convalescent phase and its association with liver functions. We performed a retrospective study to investigate the longitudinal dynamic serum cytokine, liver function and metabolomic profiles, as well as their potential correlations, from the viral replication phase to early convalescence. Our results demonstrated that liver injury was common. Liver injury was significantly associated with higher levels of interleukin (IL)-6 and IL-10 (p<0.05). However, alanine aminotransferase levels decreased during the first week after hospital discharge (p<0.01). In parallel, T cell and B cell immune response-stimulating cytokine IL-4, but not IL-2, was significantly elevated (p<0.05). Furthermore, interferon-γ (IFN-γ) and tumor necrosis factor-α (TFN-α) levels increased, in contrast to the decrease in IL-6 and IL-10 levels; liver function returned to normal. The metabolomic analysis supported active recovery during early convalescence of COVID-19 patients that had distinct metabolic profiles associated with the hepatic tricarboxylic acid cycle, amino acid metabolism, and lipid metabolism. In addition, we identified a metabolomic association of IL-4 with liver repair. Our findings suggest that discharged patients continue to recover from the physiological effects of COVID-19, and the association of IL-4, IL-6, and IL-10 levels with metabolic changes and liver function repair may have important implications for clinical manifestations and treatment of COVID-19.